Hubungan Tingkat Stress Terhadap Hipertensi Pada Lansia Di Posyandu Adiyoswa Keluharan Kedawung - Mita Putri Sugiyanto; Fida' Husain (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Stress is an expression of the human body's reaction to any demands experienced by it and is a mobilization or defense movement of the human body. Common symptoms that arise when experiencing stress are: the stress response is angry or anxious, the stress response is depressed, and the stress response is silent. Data from the Social Welfare Service of Central Java Province in 2017 recorded 704,000 people experiencing mental disorders, 608,000 people experiencing stress, and 96,000 being diagnosed with insanity. Objective: To determine the relationship between stress levels and the incidence of hypertension in the elderly at the Posyandu Lansia Adiyuswo, Kedawung Village. Methods: This research is a quantitative research with a cross sectional approach. Sampling using purposive sampling with sampling that researchers have determined certain criteria for the object to be sampled with a sample of 87 respondents. Bivariate analysis using Rank Spearman test Results: The results obtained 47 respondents, most of the elderly at Posyandu Adiyuswo Kedawung had stress levels in the moderate category as many as 25 respondents (53.2%), while most of the elderly at Posyandu Adiyuswo Kedawung had level 1 hypertension, namely as many as 26 respondents (55.3%). The results of the test The results of data analysis using the Rank - Spearman test obtained a value of Sig = 0.000 < (0.05) which means Ho is rejected and Ha is accepted. Conclusion: There is a relationship between stress levels and the incidence of hypertension in the elderly at Posyandu Adiyuswo Kedawung.